2019
DOI: 10.1002/jccs.201800412
|View full text |Cite
|
Sign up to set email alerts
|

A new green method for the synthesis of silver nanoparticles and their antibacterial activities against gram‐positive and gram‐negative bacteria

Abstract: This study aims to evaluate the capability of Ageratum conyzoides and Mikania micrantha extracts to synthesize silver nanoparticles (AgNPs) and their antibacterial capability against gram‐positive and gram‐negative bacteria. Several properties of the synthesized AgNPs, including plasmonic, biomolecule bonding, shape, size, and antibacterial, were investigated. Ultraviolet–visible (UV–vis) spectroscopy was employed for characterizing their plasmonic properties. Functional groups on the produced AgNPs were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Several studies have confirmed the correlation between the UV-vis spectrum and properties of AgNPs [24][25][26][27]. A single peak in the UV-vis spectrum can be correlated with uniform spherical AgNPs [28][29].…”
Section: Uv-vis Characteristicsmentioning
confidence: 80%
“…Several studies have confirmed the correlation between the UV-vis spectrum and properties of AgNPs [24][25][26][27]. A single peak in the UV-vis spectrum can be correlated with uniform spherical AgNPs [28][29].…”
Section: Uv-vis Characteristicsmentioning
confidence: 80%
“…The data of the inhibition halos are in agreement with the data presented in the literature. Syafiuddin et al (Nurul Aini et al, 2019 ) obtained inhibition data of 7.7 mm and 10 mm for Bacillus cereus and E. coli , respectively, using silver nanoparticles produced with the natural oxidizing agent Carica papaya . However, using the agents Manihot esculenta and Morinda citrifolia , no inhibition halo was observed (Nurul Aini et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Syafiuddin et al (Nurul Aini et al, 2019 ) obtained inhibition data of 7.7 mm and 10 mm for Bacillus cereus and E. coli , respectively, using silver nanoparticles produced with the natural oxidizing agent Carica papaya . However, using the agents Manihot esculenta and Morinda citrifolia , no inhibition halo was observed (Nurul Aini et al, 2019 ). Aini et al (Nurul Aini et al, 2019 ) studied the antibacterial capacity of silver nanoparticles produced by the extracts of Talinum triangulare , Ageratum conyzoides , and Mikania micrantha and obtained values of inhibition halo for the microorganism E. coli of 2.35 ± 0.35, 1.27 ± 0.06, and 1.3 ± 0.5, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nanomaterials are intended to enhance textile features such as self‐cleaning, water‐repellent and dirt‐repellent, antimicrobial, conductive, and antistatic properties, and decreased gas permeability and flammability . Silver nanoparticles (AgNPs) are a class of nanomaterials that have been hugely explored because of their remarkable features such as physical and mechanical . AgNPs have been recognized to have several properties such as antibacterial, antifungal, anticancer, and anti‐inflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Silver nanoparticles (AgNPs) are a class of nanomaterials that have been hugely explored because of their remarkable features such as physical and mechanical. [9][10][11][12][13][14][15][16] AgNPs have been recognized to have several properties such as antibacterial, antifungal, anticancer, and anti-inflammatory.…”
mentioning
confidence: 99%